Polycyclic aromatic hydrocarbons modulate cell proliferation in rat hepatic epithelial stem-like WB-F344 cells - Chramostová, Katerina; Vondrácek, Jan; Sindlerová, Lenka; Vojtesek, Borivoj; Kozubík, Alois; Machala, Miroslav (Toxicology and applied pharmacology, 2004)
Although many polycyclic aromatic hydrocarbons (PAHs) are recognized as potent mutagens and carcinogens, relatively little is known about their role in the tumor promotion. It is known that 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) can induce release of rat hepatic oval epithelial cells from contact inhibition by a mechanism possibly involving the aryl hydrocarbon receptor (AhR) activation. Many PAHs are AhR ligands and are known to act as transient inducers of AhR-mediated activity. In this study, effects of 19 selected PAHs on proliferation of confluent rat liver epithelial WB-F344 cells were investigated. Non-mutagens that are weak activators or nonactivators of AhR-mediated activity had no effect on cell proliferation. Relatively strong or moderate AhR ligands with low mutagenic potencies, such as benzofluoranthenes, benz[a]anthracene, and chrysene, were found to increase cell numbers, which corresponded to an increased percentage of cells entering S-phase. Strong mutagens, including benzo[a]pyrene and dibenzo[a,l]pyrene, increased a percentage of cells in S-phase without inducing a concomitant increase in cell numbers. The treatment with mutagenic PAHs was associated with an increased DNA synthesis and induction of cell death, which corresponded with the activation of p53 tumor suppressor. Apoptosis was blocked by pifithrin-alpha, the chemical inhibitor of p53. Both weakly and strongly mutagenic PAHs known as AhR ligands were found to induce significant increase of cytochrome P4501A activity, suggesting a presence of functional AhR. The results of the present study seem to suggest that a release from contact inhibition could be a part of tumor promoting effects of AhR-activating PAHs; however, the genotoxic effects of some PAHs associated with p53 activation might interfere with this process.
Keywords: nádorový supresorový protein p53; mutageny; Liver; kultivované buňky; epitelové buňky; Dose-Response Relationship, Drug; Rats; vztah mezi dávkou a účinkem léčiva; játra; apoptóza; buněčné dělení; Epithelial Cells; Receptors, Aryl Hydrocarbon; Cell Division; Tumor Suppressor Protein p53; cytochrom P-450 CYP1A1; polycyklické aromatické uhlovodíky; Mutagens; krysa rodu Rattus; Cells, Cultured; zvířata; Polycyclic Aromatic Hydrocarbons; Stem Cells; kmenové buňky; receptory aromatických uhlovodíků; Cytochrome P-450 CYP1A1; Apoptosis; Animals